PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN REKAM MEDIS ELEKTRONIK TERHADAP KEAKURATAN DATA - Firzatul Khalisha; Khoirunnisa, Rumaisha Assyifa, Sri Hajijah Purba (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
The implementation of Electronic Medical Record Management Information System (EMMRE) has become an innovative solution in improving the efficiency and accuracy of medical record data, which is an important element in clinical and operational decision making. This study aims to analyze the effect of the implementation of EMMRE on data accuracy based on a literature review of various previous studies. The research method used is a literature review approach by reviewing articles from relevant national and international journals, using keywords such as "electronic medical records," "data accuracy," and "management information systems." The results of the study indicate that the implementation of EMMRE can improve data accuracy by reducing manual errors, better data integration, and ease of access to information for medical personnel. However, challenges such as lack of user training, high implementation costs, and threats to data security remain obstacles that need to be overcome. This article provides a comprehensive overview of the benefits and constraints of EMMRE and recommends strategies to optimize its implementation in supporting data accuracy in health services.